Porphyrin/Chlorin Derivatives as Promising Molecules for Therapy of Colorectal Cancer - Fatima Dandash; David Y. Leger; Mona Diab-Assaf; Vincent Sol; Bertrand Liagre (Molecules, 2021)
Colorectal cancer (CRC) is a leading cause of cancer-related death. The demand for new therapeutic approaches has increased attention paid toward therapies with high targeting efficiency, improved selectivity and few side effects. Porphyrins are powerful molecules with exceptional properties and multifunctional uses, and their special affinity to cancer cells makes them the ligands par excellence for anticancer drugs. Porphyrin derivatives are used as the most important photosensitizers (PSs) for photodynamic therapy (PDT), which is a promising approach for anticancer treatment. Nevertheless, the lack of solubility and selectivity of the large majority of these macrocycles led to the development of different photosensitizer complexes. In addition, targeting agents or nanoparticles were used to increase the efficiency of these macrocycles for PDT applications. On the other hand, gold tetrapyrrolic macrocycles alone showed very interesting chemotherapeutic activity without PDT. In this review, we discuss the most important porphyrin derivatives, alone or associated with other drugs, which have been found effective against CRC, as we describe their modifications and developments through substitutions and delivery systems.